Chromosome aberrations induced by curcumin and aloin in Allium cepa L. root meristem cells - PALANIKUMAR, LOGANATHAN; RAGUNATHAN, IRULAPPAN; PANNEERSELVAM, NATARAJAN (Turkish journal of biology, 2011)
Bugüne hadar, çeşitli bitki bileşikleri anti-mutajenik, anti-karsinojenik ve anti-genotoksik aktivite ile ilgili kapsamlı bir biçimde çalışılmıştır. Buna rağmen, klastogenisiti bakımından bunların pek azı çalışılmıştır. Bu çalışmada, kursumin (aktif zerdeçal bileşiği) ve aloinin (aktif aloe bileşiği) klastogenik aktivitesi 4, 8, 12 saatler için 5, 10, 20, 30, 50 ve 100 μg/mL dozlarda değerlendirilmiştir. Hem kursumin hemde aloin bitki test sistemlerinde (Allium cepa L.) zamana ve doza bağlı klastogenik etkilere sahiptir. Aloin kursumine kıyasla daha klastogenikdir. Klastogenik aktivite, tüm zaman noktalarında kursumin ve aloinin çok düşük konsantrasyonlarında belirgindir. Mitotik indeks daha yüksek konsantrasyonlarda önemli derecede daha düşüktür. Ancak kursumin ve aloinin tam klastogenisiti mekanizması bitki test sistemlerinde bilinmez. To date, a variety of plant compounds have been studied extensively with regard to anti-mutagenic, anticarcinogenic, and anti-genotoxic activity. Nevertheless, very few of them have been studied in terms of clastogenicity. In the present study the clastogenic activity of curcumin (the active component of turmeric) and aloin (the active component of aloe) was evaluated at doses of 5, 10, 20, 30, 50, and 100 μg/mL for 4, 8, and 12 h. Both curcumin and aloin had significant dose- and time-dependent clastogenic effects on the test plant system (Allium cepa L.). Compared to curcumin, aloin was more clastogenic. Clastogenic activity was obvious at very low concentrations of curcumin and aloin at all time points. The mitotic index was significantly lower at higher concentrations; however, the exact mechanism of curcumin and aloin clastogenicity remains unknown in plant test systems.